Demonstratie naar de Irenehal tegen de regeringsplannen m.b.t. lonen en sociale zekerheid en tegen Bestek '81
Demonstratie naar de Irenehal tegen de regeringsplannen m.b.t. lonen en sociale zekerheid en tegen Bestek '81.